2011
DOI: 10.1111/j.1365-2249.2011.04429.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-specific T cell responses to BK polyomavirus antigens identify functional anti-viral immunity and may help to guide immunosuppression following renal transplantation

Abstract: SummaryInfection with the polyoma virus BK (BKV) is a major cause of morbidity following renal transplantation. Limited understanding of the anti-viral immune response has prevented the design of a strategy that balances treatment with the preservation of graft function. The proven utility of interferongamma enzyme-linked immunospot (ELISPOT) assays to measure T cell responses in immunocompetent hosts was the basis for trying to develop a rational approach to the management of BKV following renal transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 53 publications
2
33
0
Order By: Relevance
“…As we were unable to make the sampling intervals of these patients closer, because of patient compliance issues to their appointments, and some of their viral load values were also missing, it was not possible to analyze the relationship between viral load and BKV-specific CD4 + T-cell response in some patients. However, our results mostly confirmed that clearance of BK viremia or decrease of viral load corresponds with an increase in BKV-specific CD4+ T-cell response, similar to previous studies [19,20,22,23,26,27].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As we were unable to make the sampling intervals of these patients closer, because of patient compliance issues to their appointments, and some of their viral load values were also missing, it was not possible to analyze the relationship between viral load and BKV-specific CD4 + T-cell response in some patients. However, our results mostly confirmed that clearance of BK viremia or decrease of viral load corresponds with an increase in BKV-specific CD4+ T-cell response, similar to previous studies [19,20,22,23,26,27].…”
Section: Discussionsupporting
confidence: 93%
“…Another study that analyzed 8 renal transplant recipients with BKVN by ELISPOT using only BKV large T antigen demonstrated that an increase in BKV-specific Tcell response after reduction of immunosuppression corresponded with recovery from BKVN [27]. Later Chakera et al used all five BKV antigens individually in an ELISPOT assay in 26 renal transplant recipients and 12 healthy controls and showed that BKV-specific T-cell response was undetectable in patients with persistent viral replication or no history of BKV infection and that development of BKV-specific T-cell response was associated with viral clearance [23]. Similarly, in a longitudinal analysis of patients with BKV reactivation or BKVN; BKVspecific T-cell numbers were tested against a panel of all five antigens and it was demonstrated that an increase in BKV-specific T-cell response corresponded with recovery from BKV reactivation [22].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…QuantiFERON-CMV pp65 peptide pool Mix of 22 peptides mapped within pp65, IE-1, pp50, IE-2 and gB HCMV proteins 120 HTR (100 R+, 20 D+/R-) ELISPOT value >150 spots/2 × 10 5 PBMC and QuantiFERON-CMV value >1 to 6 IU/ml were associated with protection from HCMV infection [76] IFN-␥ ELISPOT pp65 peptide pool 48 HTR (all R+) Low responders (<50 spots/2 × 10 5 PBMC) were associated with a higher incidence of infection of immunosuppression. Additionally, the detectable IFN-␥ ELISPOT responses to all BKV antigens may be an indicator of recent or ongoing recovery from BKV infection in KTR [114]. It was shown, by using a mix of peptide pools covering all BKV antigens and multiparameter flow cytometry, that KTR with a history of rapid BKV clearance had higher frequency of multifunctional IFN-␥/IL-2/TNF-␣-producing CD4 + T cells than those with a history of severe long-lasting BKV infection [118].…”
Section: Assaymentioning
confidence: 99%
“…Restoration of BK-specific cellular immunity by tapering the immunosuppressive therapy may prevent the evolution to allograft dysfunction. Most studies have analyzed BKV-specific T-cell responses using peptide-based (large T or small T or VP1-VP3 antigens) ELISPOT assays [112][113][114][115][116][117] (Table 6). These studies suggest that BKV DNA loads are associated with low or undetectable antigen-specific Tcell responses, while resolution of active BKV infection is correlated with recovery of BKV-specific T-cell responses.…”
Section: Bkvmentioning
confidence: 99%